HARMONISASI JALINAN DAKWAH DAN POLITIK HUKUM TATA NEGARA (Wardah, 2015)
It is undeniable that Islam is a universal religion which is a blessing for the entire universe (rahmatan lil 'alamin). Universality of Islam was visible from multi-aspect doctrine, socio-religious aspects, regulate the life of mankind, and have included the inside aspect of constitutional law and political of country. This article examines how, in practice, where the Prophet Muhammad has implemented the politics of constitutional law in line with the guidance of the Qur'an, especially in the Medina period. While in Makkah, the Prophet many displays as a religious figure, namely preaching gradually namely in secret until blatant. But when in Medina seen the integration of the self Prophet Muhammad SAW. both religious figure and statesman. Besides continuing proselytizing mission, the Prophet set Medina to become a developed country and then Islam can spread to parts of the world. Today Islam has been able to become a force and are believed and practiced the teachings of the world's population and it is inseparable from the role of dakwah and politics. Both integrated and work together in the history of Islam, both in conception and implementation. To stay awake existence of Islam, the role of political propaganda and constitutional law must be optimized for the future.Relationship between the two, it was shown that the political ideal function becomes a tool to carry out the mission of preaching. On the other hand Dakwah must also be able to provide an understanding of the political importance of the State constitutional law for the advancement of religion and Muslims, and not vice versa ie away from politics because of the perception that one or manipulate dakwah for political purposes of constitutional law. To ensure that the political activities of the State constitutional law is not lost, it should be understood that in the politics of the State constitutional law is no law that must be followed, while the law is no political aspects of constitutional law which should be implemented. It will allow the synergy of political dakwah and constitutional law for the realization of the glory of Islam in national and international rankings.